The Effect of Intraoperative Glove Choice on Carpal Tunnel Pressure - Jernigan, Edward W., III; Smetana, Brandon S.; Rummings, Wayne A.; Dineen, Hannah A.; Patterson, J. Megan M.; Draeger, Reid W. (Journal of Hand and Microsurgery, 2018)
Introduction The aim of this study was to quantify the effect of surgical gown and glove wear on carpal tunnel pressure. The authors hypothesized that gowning and gloving is associated with an increase in carpal tunnel pressure in cadaveric specimens wearing appropriately sized gloves. Furthermore, they hypothesized that increased glove thickness, double gloving, and smaller-than-appropriately sized gloves would all serve to increase carpal tunnel pressure.Materials and Methods Baseline carpal tunnel pressure measurements were obtained in 11 cadaveric specimens. Each specimen was subsequently gowned and gloved. Carpal tunnel pressures were obtained for each specimen fitted with four different types of gloves in four scenarios: (1) appropriately sized gloves, (2) one full-size smaller, (3) one full-size larger, and (4) double gloved.Results Mean carpal tunnel baseline value was 3.5 mm Hg. Appropriately sized single-glove wear more than doubled baseline carpal tunnel pressure. Double gloving and smaller-than-appropriately sized glove wear more than tripled baseline values. Among the single-glove subgroup, the thickest gloves (ortho) were associated with the highest increase in pressure from baseline values.Conclusion Glove selection can have repercussions related to carpal tunnel pressure. Susceptible surgeons should consider these factors when making decisions regarding intraoperative glove wear.
Keywords: carpal tunnel pressure; carpal tunnel syndrome; double gloving; glove wear